Incidence and causes of dental trauma in children living in the county of Värmland, Sweden. Issue 1 (8th September 2015) - Lexomboon, Duangjai; Carlson, Christina; Andersson, Ragnar; von Bultzingslowen, Inger; Mensah, Tita
Abstract: Aim: The aims of this study were to determine the incidence of injuries to permanent incisors in 2011–2013 in children aged 8–10 years living in the county of Värmland, Sweden, and to compare it with the incidence rates in 1989/1990 in the county of Västmanland, as well as to determine the cause of dental trauma in relation to time and place. Method: The study analysed the patient records from dental visits (2011–2013) of trauma to the permanent incisors in children aged 8–10 years. The incidence rates were the incidence per 1000 children at risk. Standardized incidence rates were calculated for the comparison between different years. Information about month, location where the trauma occurred as well as cause of trauma was recorded. Results: A total of 2.2% of 21 721 children aged 8–10 years had experienced at least one trauma. The incidence rate in Värmland increased from 18.9 in 2011 to 21.3 in 2012 to 28.5 in 2013. The standardized incidence rate in Värmland in 2011 and 2012 was not significantly different than in Västmanland in 1989/1990 ( P  > 0.05), but the standardized rates in 2013 were significantly higher than in 1989/90 ( P  < 0.001). Dental trauma occurred most often outdoors, followed by sports arenas/sports fields, and more often at school than at home. Falling and slipping was the most common cause of trauma, followed by accidents during leisure activities, playing and sports. Conclusion: The incidence rate for dental trauma has not decreased in the past 20 years, and there is an indication that parents and teachers should be more aware of the risks of dental trauma at leisure times and at school as well as during sports and exercise.